STUDY OF EMBARGO’S AFFECT ON CANCER IN IRAQ (Baghdad Science Journal, 2004)
different ?? ? injury ? This study aims to knowing the affect of embargo on cancer tutors in Iraq according to different body systems , In addition, this '?0 kinds study aims at knowing t^e categories ages that can be mostly injured by the cancer Egression analysis and descriptive statistics( median and frequency tables). ^?^???? have been used to achieve these two aims .This study includes ah the seventy cancer s Iraq from 1980-1998 and the data have been from the Ministry of Health / ?? tumors Iraqicancer board administration / central registry. The results of this study are emale productive? : Embargo has affected the ten different body systems as .? central nervous system and opthamamology , Hematology ,Respiratory ? system system , male productive system , lymphatic system, connective and other soft tissues